2006
DOI: 10.1021/np0600088
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenoids from the Roots of Euphorbia fischeriana

Abstract: From the dried roots of Euphorbia fischeriana, seven new diterpenoids, 3alpha,17-dihydroxy-ent-pimara-8(14),15-diene (1), 7beta,11beta,12beta-trihydroxy-ent-abieta-8(14),13(15)-dien-16,12-olide (2), 17-acetoxyjolkinolide B (3), 13beta-hydroxy-ent-abiet-8(14)-en-7-one (4), 12-deoxyphorbaldehyde-13-acetate (5) 12-deoxyphorbaldehyde-13-hexadecacetate (6), and 12-deoxyphorbol-13-(9Z)-octadecanoate-20-acetate (7), and two known compounds, 12-deoxyphorbol-13-decanoate (8) and prostratin (9), were isolated. The struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 14 publications
4
37
0
Order By: Relevance
“…By the comparison of spectroscopic data with literature, the known compounds isolated from the roots of E. scheriana were identied as 11b-hydroxy-8,14-epoxy-ent-abieta-13(15)-en-16,12olide (6), 12 8b,14b-epoxy-13,15-abiatene-16,12a-olide (7), 14 jolkinolide B (8), 15 17-hydroxyjolkinolide B (9), 15 jolkinolide A (10), 15 17-hydroxyjolkinolide A (11), 16 yuexiandajisu D (12), 17 ent-11b-hydroxyabieta-8 (14),13(15)-dien-16,12b-olide (13), 16 13bhydroxy-ent-abiet-8(14)-en-7-one (14), 18 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…By the comparison of spectroscopic data with literature, the known compounds isolated from the roots of E. scheriana were identied as 11b-hydroxy-8,14-epoxy-ent-abieta-13(15)-en-16,12olide (6), 12 8b,14b-epoxy-13,15-abiatene-16,12a-olide (7), 14 jolkinolide B (8), 15 17-hydroxyjolkinolide B (9), 15 jolkinolide A (10), 15 17-hydroxyjolkinolide A (11), 16 yuexiandajisu D (12), 17 ent-11b-hydroxyabieta-8 (14),13(15)-dien-16,12b-olide (13), 16 13bhydroxy-ent-abiet-8(14)-en-7-one (14), 18 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The NMR data suggested that compound 2 was a pimaran derivative [9]. In its HMBC spectrum (Figure 2), the correlation between H-2 and the carbonyl at d C 170.3 was observed, which indicted that this acetoxyl group was at C-2 position, meanwhile, the correlation between H-7 (d H 3.40) and the carbon at d C 26.9 (C-14) suggested that a hydroxyl group was located at C-7.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain E. fischeriana transcriptome expression profiles in roots, and identify candidate genes upstream of prostratin synthesis, where traces of prostratin has been previously reported [1], Illumina technology was used to sequence an E. fischeriana library of transcripts expressed in roots generating more than 17.5 million pair-end short reads encoding 1.3 billion bases (Table 1). We initially evaluated the base quality of the sequenced reads (Additional file 1) and trimmed poor quality bases as well as removed poor quality reads (Additional file 2).…”
Section: Resultsmentioning
confidence: 99%
“…The dried plant roots of E. fischeriana and other Euphorbia species are called "Lang-Du", which means extremely toxic in Chinese. The roots have often been used in traditional Chinese medicine to treat a wide range of ailments, such as edema, ascites, and cancer [1]. Previous studies of the plant have revealed it mainly contains diterpenoids, triterpenoids and steroids [2].…”
Section: Introductionmentioning
confidence: 99%